Geographical Dimensions of Russian Energy Developments - Tykkyläinen, Markku (Louvain-la-Neuve: European Regional Science Association (ERSA), 2003)
For decades, energy production and use have been of primary importance for the economy of Russia and the former Soviet Union. These newest energy plans support the country's economic connections with the west and global economy. Many factors in energy production and logistics (and politics) promote the integration of Russia with Europe, and almost only with Europe. This economic connection between Russia and the EU countries seems to be profitable for both sides, as their economies are mutually complementary. The formation of such mutual interests causes new security configuration in the foreign policies of these countries. The former empire's parts bordering on Russia in the west, Belarus and first of all Ukraine, have become problematic due to transit payment conflicts. Consequently, the focus of logistic visions is geographically transferred to the north. Russian companies develop northern pipelines and ports as well as plan the construction of new oil and gas pipelines through Fennoscandia. On the other hand, these northern infrastructure plans are also a pure geographical coincidence, in the way that new oil and gas deposits lie in northern high-latitude zones. Logistic investments near the border regions of Finland are supported by the factor that the shortest way for gas (and partly oil) transportation to Central Europe is through the Baltic Sea area. Russian Energy plans bring about re-integration: Close cooperation between Russia and the European Union in the energy field can bring the former COMECON countries and the Baltic states, when they get EU membership, back into the energy system, from which they wanted to be separated ten yeas ago. It seems evident that the Russian Energy developments will have spin-offs to localities of the European North. How, to which areas, and to what extent is worth dicussing and elaborating on.